Production trials of fresh pasta enriched with phenolic compounds extracted from wheat by KOH-induced hydrolysis - Delvecchio, L.N.; Pasqualone, A. (Progress in Nutrition, 2013)
Some critical points may raise during the production of functional foods. Due to their peculiar physic-chemical properties, the functional compounds could alter the normal processing steps and affect the sensory acceptability of the final products. The aim of this work has been to assess the feasibility of the enrichment of fresh pasta with phenolic compounds extracted from wheat. The phenolic extracts were obtained by KOH-induced hydrolysis and were used by replacing all the processing water required for pasta-making. In particular, the aspects referring to the visco-elastic characteristics of dough and sensory properties of final product have been analysed. The obtained results showed that the enrichment negatively interfered with dough formation. In fact, the enriched dough was significantly more consistent than control dough and showed a reduced machinability. Phenol-enriched pasta was significantly browner than control pasta, with a sensory profile characterized by stronger salty and bitter taste than control pasta. The observed technologic and sensory drawbacks indicate a scarce feasibility and do not encourage to expect a good product acceptability. Further work is required to set up an efficient extraction method without any hydrolysis step. Prove di produzione di pasta fresca arricchita con sostanze fenoliche estratte dal grano mediante idrolisi con KOH Alcune criticità possono sorgere durante la produzione di alimenti funzionali in quanto le proprietà chimico-fisiche dei composti funzionali aggiunti possono alterare il normale processo produttivo e l’accettabilità organolettica dei prodotti finiti. Lo scopo del presente lavoro è stato quello di determinare la fattibilità dell’arricchimento di pasta fresca con sostanze fenoliche estratte da crusca di grano con un metodo estrattivo che prevede l’uso di KOH, sostituendo l’acqua di impastamento con pari quantità di estratto fenolico. In particolare sono state considerate le caratteristiche visco-elastiche dell’impasto arricchito e il profilo sensoriale della pasta arricchita. I risultati ottenuti mostrano che l’aggiunta di estratto interferiva negativamente con la formazione dell’impasto, più consistente e meno lavorabile del controllo. La pasta arricchita, inoltre, appariva più scura di quella convenzionale e mostrava un più accentuato sapore salato e amaro. Questi risultati inducono a presumere una scarsa fattibilità industriale a causa di una scarsa accettabilità del prodotto. Ulteriori studi dovranno essere condotti per mettere a punto efficienti metodi di estrazione delle sostanze fenoliche che non richiedano idrolisi.